Responsibility for Illegal Use of Trademarks: International and Interstate Aspects - Selivanovskaya, Julia Igorevna; Talan, Mariya Vyacheslavovna; Sboeva, Irina Mihailovna (International Journal of Criminology and Sociology, 2022)
A trademark is a widespread means of product individualization, which allows you to draw attention to the product, its manufacturer, or the seller. In fact, Goods, works, service individualization tools in the Russian Federation are the outcome of mental activity. Trademark registration makes it possible to form an easily recognizable brand and use it in order to sell it successfully among similar products. A manufacturer, promoting his product on the market, spends money on advertising, and increases the attractiveness of his products. Unscrupulous entrepreneurs are very tempted to produce goods using a famous brand, without corresponding costs, and without keeping a high quality of his goods. This article discusses the international and domestic aspects of accountability for the illegal usage of a trademark and provides recommendations for R.F. criminal law improvement. Moreover, Several investigation methods are utilized in the survey, including statistical, systematic and structural, historical and legal, formal and logical, specific sociological, as well as comparative law.